4 Educational Impact of Targeted Neonatal Echocardiography (TNE) on Neonatal-Perinatal Medicine (NPM) Subspecialty Residents. (29th October 2021) - Friedmann, Isabel; McNamara, Patrick; Bhattacharya, Soume; Cheng, Anita
Abstract: Primary Subject area: Neonatal-Perinatal Medicine Background: Targeted Neonatal Echocardiography (TNE) is a real-time cardiac imaging modality used by neonatologists who have completed a minimum of one-year training in cardiovascular physiology and imaging methodology, to optimize management of neonatal cardiorespiratory compromise. TNE is provided as a clinical service, to aid in diagnosis, treatment, and monitoring of neonatal cardiovascular illness. Potential impacts of TNE on trainee education are unknown. Objectives: This study aimed to describe trainees' perspectives on existing neonatal hemodynamics education and perceived impacts of TNE on their education. Design/Methods: This was a mixed quantitative and qualitative study that surveyed NPM subspecialty residents in Canada and the United States of America (USA), at centres both with and without TNE. Survey questions sought to explore current perspectives on cardiac and hemodynamics curriculum in training programs. Results: 92 residents responded to the survey, of whom 24 (26%) were enrolled in a program with an active TNE service, 64 (70%) were training at a non-TNE centre, and 4 (4%) were unsure. Trainees at TNE centres were more satisfied with their overall hemodynamics training (91% vs. 69%, p=0.040; Table 1). 25% of all trainees felt they do not have sufficient hemodynamics training to prepare them for independent practice. On analysis of curriculum content, cardiac development, myocardial functioning in prematurity, and cardiac mechanics emerged as areas of knowledge gaps among all residents (Table 2). TNE centre trainees reported that bedside TNE teaching offers immediate insights into how patients respond to management decisions, while didactic TNE teaching allows for learning at a slower pace, with appropriate knowledge consolidation. Only 9% of respondents at TNE sites reported a formal process of hemodynamics review between clinical and TNE teams. 90% of respondents believed that a TNE service would positively impact their hemodynamics education by improvement in knowledge of cardiovascular physiology and management decisions. Conclusion: Most trainees believed that TNE may be a valuable educational tool, with current perceived satisfaction with overall hemodynamics training higher among residents training at TNE centres. 25% of all trainees felt unprepared for transitioning to independent practice. Hence, thoughtful curriculum design for real-time and consolidation learning, with specific emphasis on content gaps, as well as working toward a formal process of hemodynamics review, should be considered.